How much of the Caatinga is legally protected? An analysis of temporal and geographical coverage of protected areas in the Brazilian semiarid region - Teixeira, Lucas Peixoto; Lughadha, Eimear Nic; Silva, Marcus Vinicius Chagas da; Moro, Marcelo Freire (Acta Botânica Brasílica, 2021)
ABSTRACT Tropical dry forests are among the most threatened vegetation types in the world, exposed to even higher deforestation rates than rainforests. The largest tropical dry forest is the Caatinga, in the semiarid Northeast region of Brazil. Home to many endemic species and genera, the Caatinga has lost half of its original vegetation cover and become highly fragmented. Furthermore, the Caatinga is little protected by conservation units and subject to multiple human pressures. Brazil committed to the Convention of Biological Diversity’s Strategic Plan for Biodiversity 2011 -2020, including the Aichi Biodiversity Targets, requiring protection of 17 % of terrestrial habitats. Using GIS, we quantified the total area of Caatinga encompassed by fully protected and sustainable use reserves. We found that less than 8 % of the Caatinga is legally protected under Brazil’s national nature reserve legislation (SNUC law), and only 1.3 % is in reserves with full legal protection. We show that the geographical distribution of reserves is biased, leaving some regions of the Caatinga with very little protection. We conclude that Brazil has not met international conservation commitments with respect to the Caatinga and, despite a recent expansion of the protected area network, only small and unrepresentative portions of the Caatinga are effectively safeguarded.